2017
DOI: 10.1016/j.jare.2016.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Uric acid in the pathogenesis of metabolic, renal, and cardiovascular diseases: A review

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
165
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 289 publications
(187 citation statements)
references
References 192 publications
3
165
0
4
Order By: Relevance
“…The prevalence of hyperuricaemia was found to be 32.6% in T2DM patients with central obesity, which was far above that of the general population. HUA has proven to be an independent predictor of the development and progression of diabetic nephropathy . Additionally, elevated serum uric acid (SUA) levels have been associated with increased risk of hypertension and cardiovascular disease in individuals with T2DM .…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of hyperuricaemia was found to be 32.6% in T2DM patients with central obesity, which was far above that of the general population. HUA has proven to be an independent predictor of the development and progression of diabetic nephropathy . Additionally, elevated serum uric acid (SUA) levels have been associated with increased risk of hypertension and cardiovascular disease in individuals with T2DM .…”
Section: Introductionmentioning
confidence: 99%
“…UA is considered as a biomarker of oxidative stress. UA acts as a pro‐oxidant inside the cell to stimulate nicotinamide adenine dinucleotide phosphate oxidase enzyme causing increased intracellular oxidative stress and mitochondrial injury (Becker, ; Sharaf El Din, Salem, & Abdulazim, ). In the present study, the intensity of the final oxidized product of purine metabolism (UA) was significantly increased (Supporting information Table S4) in the renal tissues of rats in the high‐dose groups, which may be related to Cd‐induced oxidative stress in kidneys.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have shown that glomerular lesions lead to reduced UA filtration, and renal tubular lesions lead to reduced UA secretion, which cause elevated serum UA. The elevated UA in the body can act directly on the kidneys and is an independent risk factor for the development of chronic kidney disease (Barkas, Elisaf, Liberopoulos, Kalaitzidis, & Liamis, ; Sharaf El Din et al, ). In the present study, the renal tubule injury markers, such as the levels of β2‐MG, RBP and (NAG)/CR, were significantly increased, and the level of UA was significantly decreased (Table ) in urine in the high‐dose group, all of which further supported the fact that the renal tubules were damaged.…”
Section: Discussionmentioning
confidence: 99%
“…The kernel parameter 1/2σ 2 and c 2 search ranges are [2 −8 , 2 8 ] in steps of 2 0 5 for Gaussian, semi-local, exponential, inverse multiquadric, rational, and Kmod kernels. The kernel parameter d search ranges are [1,5] in steps of 1 for polynomial kernel. For kernel PLS, the search ranges are [1,30] in steps of 1 for the number of latent variants N lv .…”
Section: Methodsmentioning
confidence: 99%
“…Fast and accurate determination is very essential to the early diagnosis of the diseases. For instance, the serum uric acid (UA) level can be used as an indicator for the detection of diseases related to purine metabolism [1][2][3] and leukemia pneumonia [4][5][6]. Various analytical methods are developed for the determination of UA.…”
Section: Introductionmentioning
confidence: 99%